Capillary Evaporation‐Induced Fabrication of Compact Flake Graphite Anode with High Volumetric Performance for Potassium Ion Batteries - Chang, Xiaqing; Sun, Ning; Li, Guang; Yang, Botao; Soomro, Razium A.; Xu, Bin (Advanced materials interfaces, 2023)
Improvement in volumetric performance is growing requirements for rechargeable batteries of lightweight and compact size. Flake graphite (FG) with thin lamellar structure realizes a satisfactory K‐ion storage performance, but its low packing density leads to poor volumetric capacity. Herein, this work fabricates an FG anode with improved packing density by hydrothermal treatment of the FG with graphene oxide and subsequent capillary evaporation‐induced drying process. A three‐dimensional flake graphite/reduced graphene oxide (FG/rGO) hydrogel is formed after hydrothermal treatment, which can be compressed during drying process via the capillary force generated by water evaporation, resulting in a compact structure with enhanced packing density. Compared to the pristine FG electrode (106.0 mAh cm−3), the FG/rGO‐82 anode realizes an ultrahigh volumetric capacity of 218.9 mAh cm−3 and good rate performance with a retained capacity of 152.3 mAh cm−3 at 2 C. Moreover, the FG/rGO‐82 exhibits excellent cycle stability with a capacity retention of 90.1% after 300 cycles. Even under a high mass loading of 7.4 mg cm−2, it still remains a volumetric capacity of 145.4 mAh cm−3 after 300 cycles at 1 C. The results prove that the capillary evaporation induced drying of hydrogel is an effective way to prepare electrode material with high volumetric capacity. A flake graphite anode with improved packing density is fabricated by hydrothermal treatment with the assistance of graphene oxide and subsequent capillary evaporation‐induced drying process. The obtained flake graphite/reduced graphene oxide (FG/rGO‐82) anode realizes a high K‐ion storage volumetric capacity of 218.9 mAh cm−3 with a high initial coulombic efficiency (ICE) of 81.0%, as well as excellent cycle and rate capability.